(untitled) (Homoeopathy for All, 2024)
An integrative approach combining conventional and alternative therapies like homeopathy is essential for a holistic management of pancreatic disorders. This approach acknowledges the complex etiology of these diseases and caters to diverse patient needs, enhancing patient care through combined insights from conventional medicine and holistic practices.